2021
DOI: 10.7717/peerj.11912
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from the resurrected family Polyrhabdinidae Kamm, 1922 (Apicomplexa: Gregarinomorpha) supports the epimerite, an attachment organelle, as a major eugregarine innovation

Abstract: Background Gregarines are a major group of apicomplexan parasites of invertebrates. The gregarine classification is largely incomplete because it relies primarily on light microscopy, while electron microscopy and molecular data in the group are fragmentary and often do not overlap. A key characteristic in gregarine taxonomy is the structure and function of their attachment organelles (AOs). AOs have been commonly classified as “mucrons” or “epimerites” based on their association with other cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
(151 reference statements)
1
11
0
Order By: Relevance
“…Our studies [55][56], and the observations performed by Hiillos with co-authors [57] showed that the gregarines were widely distributed in the populations of P. elegans, where most polychaete specimens harbored these parasites. Authors also noted that the variation in the prevalence of gregarines between polychaete populations, characteristic of S. pygospionis and P. pygospionis, is a common feature of parasitic apicomplexans.…”
Section: Impact Of the Metchnikovellids On Gregarinessupporting
confidence: 58%
See 1 more Smart Citation
“…Our studies [55][56], and the observations performed by Hiillos with co-authors [57] showed that the gregarines were widely distributed in the populations of P. elegans, where most polychaete specimens harbored these parasites. Authors also noted that the variation in the prevalence of gregarines between polychaete populations, characteristic of S. pygospionis and P. pygospionis, is a common feature of parasitic apicomplexans.…”
Section: Impact Of the Metchnikovellids On Gregarinessupporting
confidence: 58%
“…According to an alternative idea, the sporoplasm causes invagination of the host plasma membrane in the contact zone between the manubrium and the area of a gregarine micropore, where the pellicle is thin [30], [34]. It should be noted that archigregarines S. pygospionis and eugregarines P. pygospionis have numerous micropores on their cell surface, at the bottom of cortical grooves and on the sides of epicytic folds, respectively [55][56]. A similar mechanism of invagination of the host plasma membrane in the contact zone between the penetration tube and the host cell (a kind of invasion synapse) is suggested for aphelids, holomycotan parasitoids of algae, closely related to fungi, and Rozella spp., parasitoids of zoosporic fungi and oomycetes, closely related to microsporidia [59].…”
Section: Impact Of the Metchnikovellids On Gregarinesmentioning
confidence: 99%
“…This species can be a dominant member of benthic communities (Bolam, 2004; Bolam & Fernandes, 2003) and is an important prey item for other invertebrates and fish (Mattila, 1997). Pygospio elegans is known to host at least two apicomplexan symbionts: the archigregarine Selenidium pygospionis (Paskerova et al, 2018) and the eugregarine Polyrhabdina pygospionis (Paskerova et al, 2021), which both inhabit the worm's intestine. In our previous study of the host's transcriptome (Heikkinen et al, 2017), we detected the presence of a third apicomplexan symbiont.…”
Section: Methodsmentioning
confidence: 99%
“…Amplification efficiency of the primers was estimated to be 94.3% (slope = −3.465, r 2 = .997) using a qPCR. To demonstrate the specificity of the designed primers, the assay was checked against other apicomplexan DNA that might be present in the host gut; S. pygospionis (Archigregarinorida) (Paskerova et al, 2018) and P. pygospionis (Eugregarinorida) (Paskerova et al, 2021). Individual S. pygospionis ( n = 88) and P. pygospionis ( n = 33) cells were isolated from P. elegans collected in September 2020 (St. Petersburg, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies also demonstrated no effect at all [ 54 ]. Our studies [ 55 , 56 ], and the observations performed by Hiillos with co-authors [ 57 ], showed that the gregarines were widely distributed in P. elegans populations, in which most polychaete specimens harbored these parasites. The prevalence of gregarines S. pygospionis and P. pygospionis varied among populations of polychaetes, which is a common feature of apicomplexan parasites [ 57 ].…”
Section: The Impact Of Metchnikovellids On the Host–parasite System “...mentioning
confidence: 51%